Adolescents And Peer Attachment: Attachment Styles, Peer Trust, Communication, And Alienation In Light Of Gender - بوالصوف نجلاء; سعادو أسماء (مجلة دراسات في سيكولوجية الانحراف, 2024)
he current study aimed to explore attachment styles, dimensions, and levels of peer attachment among Algerian adolescents in light of their gender through studying the differences in the average degrees of each one of peer attachment determinants among the study sample. In addition, it aims to determine the levels, dimensions, and styles of peer attachment that are most prevalent among the adolescents of study sample. In order to achieve this goal, a quantitative research was carried out relying on the descriptive analytical approach, through which the emotional attachment scale for adolescents in its form of attachment to friends by Abdul Rahman and Al Omari (2014) (codified by the researchers) was applied on a sample consisting of (130) adolescents. The study resulted in the following findings: the ‘high level’ of peer attachment, the dimension of ‘peer trust’, and the ‘secure attachment style’ are the most prevalent among the study sample, and although there were no statistically significant differences in light of gender in all determinants of peer attachment among the sample members, a statistically significant difference in peer communication is present, in which the differences are in favor of females.